Norway : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
In 2003, domestic and external factors in Norway slowed real GDP growth to an estimated 0.5 percent. With inflation pressures waning, Norges Bank cut interest rates aggressively. The non-oil fiscal position has deteriorated somewhat over the past two years, only partly reflecting the cycle. Discussions covered the short-term outlook and policy options, the monetary and fiscal policy frameworks, aging and long-term fiscal sustainability, and structural reform. The financial system has weathered the downturn, though with some weakening of profitability.